Design of a Control System for Hybrid Quadcopter Tilt Rotor Based on Backward Transition Algorithm - Darwito, Purwadi Agus; Agustina, Nilla Perdana; Ahnaf, Hudzaifa Dhiaul; Roosydi, Syahrizal Faried; Pratama, Detak Yan; Biyanto, Totok Ruki (Journal of Robotics and Control (JRC), 2025)
An Unmanned Aerial Vehicle (UAV) is an unmanned aerial vehicle that can be controlled using either automatic or manual control. UAVs are divided into two types: rotary-wing, which uses rotating propellers to fly the aircraft, and fixed-wing, which uses fixed wings to fly the aircraft. One of the advanced developments in UAV technology is the Hybrid Vertical Take-Off Landing Quadrotor Tiltrotor Aircraft (QTRA) system, which combines the quadrotor UAV system, classified under rotary-wing, with the fixed-wing UAV system. This allows for vertical takeoff and landing as well as the ability to cruise at maximum speed. In the transition between flight modes, from quadcopter to fixed-wing and vice versa, the transition is carried out by changing the thrust direction of the two front UAV rotors from horizontal to vertical and vice versa. The change in thrust angle on the rotor is referred to as a tilt rotor. The problem that arises from changing the aircraft mode from fixed-wing to quadcopter is controlling the UAV's transition mode, which must not lose its lift force. Therefore, the tilt angle must be changed as quickly as possible. To solve this issue, a Hybrid VTOL Quadrotor Tiltrotor aircraft concept was designed with fast response, controlled by a Proportional Derivative (PD) controller. The results of the PD control system response were tested in simulations by observing the X and Z positions of the UAV, which can stabilize the position during the transition. The success criteria targeted for a stable response include a tilting angle with a settling time of 7 seconds, an overshoot height of 16 meters, and a steady-state error approaching zero. From the transition simulation tests, the system response data showed performance with an X-axis settling time of 37 seconds, a steady-state error value of 0.1 meters, and an overshoot of 0.4%.